Visual training in hemianopia alters neural activity in the absence of behavioural improvement: a pilot study - Larcombe, S; Kulyomina, Y; Antonova, N; Ajina, S; Stagg, C; Clatworthy, P; Bridge, H (Wiley, 2018)
Background Damage to the primary visual cortex (V1) due to stroke often results in permanent loss of sight affecting one side of the visual field (homonymous hemianopia). Some rehabilitation approaches have shown improvement in visual performance in the blind region, but require a significant time investment. Methods Seven patients with cortical damage performed 400 trials of a motion direction discrimination task daily for five days. Three patients received anodal tDCS during training, three received sham stimulation and one had no stimulation. Each patient had an assessment of visual performance and a functional magnetic resonance imaging (fMRI) scan before and after training to measure changes in visual performance and cortical activity. Results No patients showed improvement in visual function due to the training protocol, and application of tDCS had no effect on visual performance. However, following training, the neural response in motion area hMT+ to a moving stimulus was altered. When the stimulus was presented to the sighted hemifield, activity decreased in hMT+ of the damaged hemisphere. There was no change in hMT+ response when the stimulus was presented to the impaired hemifield. There was a decrease in activity in the inferior precuneus after training when the stimulus was presented to either the impaired or sighted hemifield. Preliminary analysis of tDCS data suggested that anodal tDCS interacted with the delivered training, modulating the neural response in hMT+ in the healthy side of the brain. Conclusions Training can affect the neural responses in hMT+ even in the absence of change in visual performance.